The Demand for Fact-Checking - Felix Chopra; Ingar K. Haaland; Christopher Roth (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Using a large-scale online experiment with more than 8,000 U.S. respondents, we examine how the demand for a politics newsletter changes when the newsletter content is fact-checked. We first document an overall muted demand for fact-checking when the newsletter features stories from an ideologically aligned source, even though fact-checking increases the perceived accuracy of the newsletter. The average impact of fact-checking masks substantial heterogeneity by ideology: fact-checking reduces demand among respondents with strong ideological views and increases demand among ideologically moderate respondents. Furthermore, fact-checking increases demand among all respondents when the newsletter features stories from an ideologically non-aligned source.
Keywords: D83; D91; L82; 330; fact-checking; news consumption; information; media bias; belief polarization